"Of spelling errors and historical distortions: historians museums and the way forward': oral traditions concerning the identity of Maziriri, the Svikiro of the Chivi people - Mazarire, Gerald C. (2016)
Colonial misspellings have caused untold havoc on the nation's local history. Historians, Museums and the nation at large have a role to play in correcting the various distortions left by the colonial regime. By overrelying on colonial sources for the reconstruction of the nation's past historians have not only perpetuated these distortions but in some cases, actually authenticated them.